Labaratory capacity of differential anemia diagnosis - L. M. Meshсheryakova; A. A. Levina; M. M. Tsybulskaya; T. V. Sokolova (Онкогематология, 2015)
The paper presents the laboratory values by which modern differential diagnosis of anemias can be performed. This takes into account a widerange of laboratory tests, including: serum ferritin, erythrocyte ferritin, serum iron, total serum iron binding capacity, iron transferrin saturation,transferrin, transferrin receptor, serum vitamin B12, erythrocyte vitamin B12, serum folate, erythrocyte folate, hepsidin, HIF-1 (hypoxiainducible factor-1), immunoglobulins on erythrocytes end others. The combination of these studies helps to accurate diagnosis and appropriate therapy.